1986
DOI: 10.1007/bf01358166
|View full text |Cite
|
Sign up to set email alerts
|

The rheology of polymeric liquid crystals

Abstract: The molecular theory of Doi has been used as a framework to characterize the rheological behavior of polymeric liquid crystals at the low deformation rates for which it was derived, and an appropriate extension for high deformation rates is presented. The essential physics behind the Doi formulation has, however, been retained in its entirety. The resulting four-parameter equation enables prediction of the shearing behavior at low and high deformation rates, of the stress in extensional flows, of the isotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…It was shown that the negative normal stress region roughly corresponds to the transition from tumbling to nonperiod conditions, encompassing the small y range of the oscillating regime [589], and that a kink appears in the viscosity curve in the same region. with extensional data over nearly three decades of elongation rate and shearing data over six decades of shear rate has been obtained for a hydroxypropylcelluloselglacial aClltic acid lyotropic system [592].…”
Section: Models For Interpretation and Correlationmentioning
confidence: 99%
“…It was shown that the negative normal stress region roughly corresponds to the transition from tumbling to nonperiod conditions, encompassing the small y range of the oscillating regime [589], and that a kink appears in the viscosity curve in the same region. with extensional data over nearly three decades of elongation rate and shearing data over six decades of shear rate has been obtained for a hydroxypropylcelluloselglacial aClltic acid lyotropic system [592].…”
Section: Models For Interpretation and Correlationmentioning
confidence: 99%
“…Bercraft and Metzner 16 performed a "molecular approach" based on a modification of the molecular theory of Doi for liquid crystalline polymers 17,18 to take into account the macroscopic dimensions of the fibers. They obtained good predictions for steady rheological measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The modified Doi model [2] was employed as a constitutive equation. The orientation of the molecules was described by an orientational order parameter tensor…”
Section: Basic Equationsmentioning
confidence: 99%
“…In the numerical simulation of the flows in complex geometries, Doi model [1] with the quadratic closure was used to clarify the general appearance of molecular orientation induced by complex flow fields, despite lack of tumbling. Numerical simulations for complex flows of LCPs using the modified Doi model [2] were carried out [3−6] . Most numerical computations, however, treated two-dimensional flows and the three-dimensional orientational behavior in complex flow fields has not been understood sufficiently.…”
Section: Introductionmentioning
confidence: 99%